Teaching Christian Ethics in Russian Public Schools: The Testing of Russia's Church-State Boundaries - Glanzer, Perry (A journal of church and state, 1999)
Perry Glanzer; Teaching Christian Ethics in Russian Public Schools: The Testing of Russia's Church-State Boundaries, Journal of Church and State, Volume 41, Iss